The Influence of Knowledge Sharing on the Performance of LPI Al-Muttaqin Foundation Employees in Tasikmalaya City: English - Lovei Miftahul Jannah; Dian Indiyati (International Journal of Economics, Business and Innovation Research, 2024)
The competition among organizations today has become very intense, including competition in educational institutions. The quality and image of a good educational institution are important factors for its appeal in the eyes of the community. One way to improve the quality and image of an organization is by increasing human resources. (SDM). This research aims to understand how the application of knowledge donating, knowledge collecting, and employee performance at the Al-Muttaqin Foundation's LPI in Tasikmalaya is based on a questionnaire distributed to the human resources of the Al-Muttaqin Foundation. This study utilizes data from 110 respondents based on the questionnaires that have been distributed. The results of this study indicate that knowledge donating and knowledge collecting have a significant impact on employee performance, with a value of 95.8%. The findings of this research contribute to the literature review regarding the relationship between knowledge donating, knowledge collecting, and employee performance, thereby potentially affecting employee performance in educational institutions.